Management of genital prolapse with vaginal pessary in La Paz, Bolivia: Case series - Arratia Mamani, Saúl Juan (2025)
Introduction. Pelvic organ prolapse is a condition commonly treated by gynecologists. Although surgical treatment is generally considered the primary option, many women prefer to start with conservative treatments or are not candidates for invasive procedures for various reasons. Case Presentation. This article presents 4 clinical cases with the aim of illustrating how the vaginal pessary can be an effective and first-line option in the treatment of advanced genital prolapse. Conclusion. In cases of advanced or exteriorized prolapse, the vaginal pessary is a widely recognized and recommended option. However, its use may be limited in some regions due to a lack of access to this resource or the reluctance of certain gynecologists to implement it.